Ragam Aplikasi dalam Pembelajaran Bahasa Arab - Manoppo, Ningsih; Aliyya Laubaha, Siti; Basarata, Nurhanifa (Assuthur: Jurnal Pendidikan Bahasa Arab, 2022)
This research aims to find out the variety of applications that can be utilised and used by teachers in learning Arabic. This research uses the library research method. The author obtained data through books, journals, articles related to the research. This research analyses the data by describing the results obtained. The results of the study are that currently there are many applications that support the learning process in accordance with the development of science and technology today. In the era of 4.0 towards 5.0 educators are required to be able to operate the available educational technology so that learning can be easier and more interesting not only monotonous so that students feel bored and bored. Therefore, applications are provided as learning support. Especially in foreign language learning such as Arabic. The applications used include duolingo, canva, youtube, mu'jam al-ma'any, edmodo, arabic anlocked, online arabic programme, learning arabic speak arabic, secil, drops, memrise, kahoot, and facebook.